A cuckoo bird-inspired meta-heuristic algorithm for optimal short-term hydrothermal generation cooperation. Issue 1 (31st December 2016) - Nguyen, Thang Trung; Ngoc Vo, Dieu; Dinh, Bach Hoang
Abstract: Optimal short-term hydrothermal generation cooperation (OSTHTGC) is used to determine the optimal operation strategy for cascaded hydropower plants and thermal plants. In this problem, equality constraints consisting of water time delay, reservoir volume, continuity water and power balance, as well as inequality constraints related to the limits of thermal and hydro generations are taken into account. In this paper, a Cuckoo Bird-Inspired Meta-Heuristic Algorithm (CBIA), which is advanced by using only few control parameters and high success rate, has been proposed to solve the OSTHTGC problem. The proposed method is applied for four test cases where the valve point loading effects of thermal units and the combination operation of a four-cascaded reservoir system are considered. The comparison of obtained results has revealed that that CBIA method is an efficient method with high quality solution and fast convergence speed compared to other relevant approaches.